2022
DOI: 10.3390/ijms23169374
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Cytochrome P450 3A5 Inhibitors: An Extensive Virtual Screening through Molecular Docking, Negative Image-Based Screening, Machine Learning and Molecular Dynamics Simulation Studies

Abstract: Cytochrome P450 3A5 (CYP3A5) is one of the crucial CYP family members and has already proven to be an important drug target for cardiovascular diseases. In the current study, the PubChem database was screened through molecular docking and high-affinity molecules were adopted for further assessment. A negative image-based (NIB) model was used for a similarity search by considering the complementary shape and electrostatics of the target and small molecules. Further, the molecules were segregated into active and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Although originally developed for molecular docking screens, DUD-E's decoys are also used as inactives in LBVS [43][44][45][46][47][48] . A recent study showed that the superior enrichment efficiency in convolutional neural network models for SBVS was achieved in the DUD-E dataset because of hidden bias in this dataset rather than a successful generalization of the pattern of protein-ligand interactions 49 .…”
Section: (Ii) Using Dud-e Decoys As Inactivesmentioning
confidence: 99%
“…Although originally developed for molecular docking screens, DUD-E's decoys are also used as inactives in LBVS [43][44][45][46][47][48] . A recent study showed that the superior enrichment efficiency in convolutional neural network models for SBVS was achieved in the DUD-E dataset because of hidden bias in this dataset rather than a successful generalization of the pattern of protein-ligand interactions 49 .…”
Section: (Ii) Using Dud-e Decoys As Inactivesmentioning
confidence: 99%